Evaluating parental experiences in using technology for remote learning to teach students with special needs during the COVID-19 pandemic - Sankoh, Alfred; Hogle, Jared; Payton, Melinda; Ledbetter, Karen (Frontiers in Education, 2023)
ABSTRACT Background: The 2020–2021 school year shut down because of the CoVid-19 pandemic brought an unprecedented burden on parents, especially those with special needs children. Parents with children with special needs were left to assist their children with remote learning at home using technology for the first time. These students with special needs were used to face-to-face and one-to-one classroom learning by skilled educators but are now left to be educated by their parents. Objective: This study explored parents’ experiences assisting their special needs children with remote learning for the first time, using technology at home during the CoVid-19 pandemic. Method: A transcendental (descriptive) phenomenology was undertaken to explore the experiences of nine participants, recruited from two school divisions in Manitoba, Canada, on their child’s education and the challenges they experienced during remote learning from home. A purposive sampling technique was used, and data were collected through telephone interviews. Results: Eight out of nine parents reported a negative experience with remote learning. Four major themes emerged after the data analysis: fear and anxiety, maintaining routines, behavioural changes and mental health, and home support. Furthermore, results indicated that integrating technology in remote learning for students with special needs was ineffective. Conclusion: This study suggests poor communication between parents and teachers, and parents’ desire to be involved in planning remote learning for students with special needs during the CoVid-19 pandemic lockdown was not met. This study also suggests that schools failed to meet students’ IEPs during remote learning. Furthermore, this study highlights that remote learning for special-needs students is inappropriate without educational assistance.